1989
DOI: 10.1002/ardp.19893221203
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Antiproliferative Effects of Amino Acid Antagonists Targeting for Aminoacyl‐tRNA Synthetases Part I ‐ The Antibacterial Effect

Abstract: Amino acid antagonists with proven or potentially inhibitory activities on aminoacyl-tRNA synthetases were tested for their antiproliferative effect against E. coli B. The compounds 4- and 6-fluoro-tryptophan, 5-methyltryptophan, selenocystine and beta-(2-thienyl)alanine gave strong growth inhibition in minimal medium, which disappeared after addition of structurally related natural amino acids or in an enriched broth. The inhibitory effect on amino-acyl-tRNA synthetases and the minimal inhibitory concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
(2 reference statements)
1
1
0
Order By: Relevance
“…This finding suggests that tryptophan biosynthesis is an unlikely target of 6-aminoindole antibacterial activity in human serum. In support of this, we found that 5-methylindole and 5-methyltryptophan, known to target tryptophan biosynthesis (Laske et al, 1989), possessed antibacterial activity in minimal media but not serum (Table S5). On the other hand, tests with 4-and 5-aminoindole, as well as 5-aminotryptophan, showed that these molecules had antibacterial activity in both minimal media and serum, indicating that the amine substituent is critical for serum activity (Table S5).…”
Section: -Aminoindole Targets Tryptophan Biosynthesis In Minimal Media But Not In Serumsupporting
confidence: 54%
“…This finding suggests that tryptophan biosynthesis is an unlikely target of 6-aminoindole antibacterial activity in human serum. In support of this, we found that 5-methylindole and 5-methyltryptophan, known to target tryptophan biosynthesis (Laske et al, 1989), possessed antibacterial activity in minimal media but not serum (Table S5). On the other hand, tests with 4-and 5-aminoindole, as well as 5-aminotryptophan, showed that these molecules had antibacterial activity in both minimal media and serum, indicating that the amine substituent is critical for serum activity (Table S5).…”
Section: -Aminoindole Targets Tryptophan Biosynthesis In Minimal Media But Not In Serumsupporting
confidence: 54%
“…Given the lack of sequence similarity and also that the aminoacylation process is essential in all living organisms, these enzymes make attractive antibacterial targets against which to develop compounds that selectively inhibit the prokaryotic synthetase and the design of such inhibitors has attracted much theoretical and practical interest ( , ). A number of tRNA synthetase inhibitors are known, including substrate analogues ( , ) and natural products ( ). An important demonstration of the potential of this approach is shown by mupirocin (pseudomonic acid-A, PS-A), which specifically inhibits bacterial isoleucyl tRNA synthetases while being ca.…”
mentioning
confidence: 99%